Nutritional evaluation of the lipid fraction of Iberian red deer (Cervus elaphus hispanicus) tenderloin. - Quaresma, M a G; Trigo-Rodrigues, I; Alves, S P; Martins, S I V; Barreto, a S; Bessa, R J B (Meat science, 2012)
The meat lipid fraction of psoas major muscle from 20 adult (10 males and 10 females) feral Iberian red deer (Cervus elaphus hispanicus) was characterized by quantification of total fat, total cholesterol, vitamin E and fatty acid (FA) composition, including detailed trans octadecenoate isomers and conjugated linoleic acid (CLA) isomeric profile. The total lipid content revealed a very lean meat (0.99 g/100g of meat), with total cholesterol content averaging 55.6 mg/100g of muscle. The FA profile displayed a very high PUFA level for ruminant meat (30.2g/100g FA). The 18:2 cis-9,trans-11 content was fairly low (0.26% of total FA) compared with other ruminant meats. The comparison of stags and hinds showed more similarities than differences. Nevertheless, hinds displayed superior contents of α-tocopherol and trans MUFA and a better n-6/n-3 ratio than stags.
Keywords: cervus elaphus hispanicus; Cholesterol; CLA; Fatty acid profile; meat quality; Vitamin E

Prediction of the feeding background of Iberian pigs using the fatty acid profile of subcutaneous, muscle and hepatic fat. - Ruiz, J; Cava, R; Antequera, T; Martín, L; Ventanas, J; López-Bote, C J (Meat science, 1998)
Thirty Iberian pigs weighing 95 kg were randomly distributed into three groups of 10 animals each and fattened in three traditional management systems ['montanera' (MO), fed extensively on acorns, 'cebo' (CE) fed on a commercial diet and 'recebo' (RE), fed on acorns and a commercial diet]. Fatty acids from the Masseter muscle, lard and liver were analysed. In the lard, fatty acid profiles from MO and RE pigs presented minor differences; however, in the liver, RE pigs showed differences to MO pigs in most of the fatty acids studied. This suggests that the muscle and especially the liver fatty acid profile reflects the feeding regime during the last phase of feeding, while the lard reflects longer term differences.
Keywords: Fatty acid profile; Feeding regime (voyant); iberian pig